Trends in fireside corrosion damage to superheaters in air and oxy-firing of coal/biomass - Hussain, Tanvir; Syed, Adnan U.; Simms, Nigel J. (Elsevier, 2013)
This paper compares the laboratory-based fireside corrosion tests on superheater/reheater materials in simulated air-firing combustion conditions with oxy-firing combustion conditions (with hot gas recycling before flue gas de-sulphurisation). The gaseous combustion environment was calculated based on a specific co-firing ratio of CCP with Daw Mill coal. The fireside corrosion tests were carried out using the “deposit recoat” test method to simulate the damage anticipated in specific environments. A synthetic deposit (Na2SO4:K2SO4:Fe2O3 = 1.5:1.5:1 mol.) which has commonly been used in fireside corrosion screening trials and is a mix that forms alkali-iron tri-sulphate (identified in many investigations as a cause of fireside corrosion) was used in these tests. The air-fired tests were carried out at temperatures of 600, 650 and 700 °C and oxy-fired tests were carried out at temperatures of 600, 650, 700 and 750 °C to represent the superheater/reheater metal temperatures anticipated in future power plants with and without synthetic deposits, with four candidate materials: T92, HR3C and 347HFG steels; nickel-based alloy 625 (alloy 625 was only tested with screening deposits). The progress of the samples during their exposures was measured using mass change methods. After the exposures, the samples were examined by SEM/EDX to characterise the damage. To quantify the metal damage, pre-exposure micrometre measurements were compared to the post-exposure image analyser measurements on sample cross-sections. The trends in corrosion damage in both air and oxy-firing conditions showed a “bell-shaped” curve, with the highest metal damage levels (peak) observed at 650 °C for air-firing and 700 °C for oxy-firing tests. However, at 600 and 650 °C similar damage levels were observed in both environments. The shift in peak corrosion damage in oxy-firing condition is believed to be the presence of higher levels of SOx, which stabilised the alkali-iron tri-sulphate compounds. Generally, in both air and oxy-firing conditions the mean metal damage was reduced with increasing the amount of Cr in the alloys. However, at the highest temperatures in both air-firing (700 °C) and oxy-firing conditions (750 °C) the metal damage of nickel based superalloy 625 was higher than HR3C.